AL Amyloidoma of the Skin/Subcutis: Cutaneous Amyloidosis, Plasma Cell Dyscrasia or a Manifestation of Primary Cutaneous Marginal Zone Lymphoma?. (August 2017) - Walsh, Noreen M.; Lano, Ian Marie; Green, Peter; Gallant, Christopher; Pasternak, Sylvia; Ly, Thai Yen; Requena, Luis; Kutzner, Heinz; Chott, Andreas; Cerroni, Lorenzo
Abstract : It is unclear whether AL amyloidoma of the skin/subcutis represents a distinct entity, an indolent precursor of systemic amyloidosis, or a manifestation of cutaneous marginal zone lymphoma (cMZL). We collected 10 cases of cutaneous AL amyloidoma in order to better characterize the clinicopathologic features of this elusive entity (M:F=4:6; median age: 62.5 y, range: 31 to 82 y). Nine patients had a solitary nodule or plaque on the lower extremity (n=7), upper extremity (n=1), or chin (n=1). One patient had an AL amyloidoma on the right thigh and a second lesion on the right arm showing histopathologic features of cMZL without amyloid deposits. Clinical investigations excluded relevant systemic disease in all cases. Microscopically, dermal/subcutaneous deposits of amyloid were associated with sparse to moderate perivascular infiltrates of lymphocytes and monotypic plasma cells (7 with kappa and 3 with lambda light chain restriction). The plasma cells expressed CD56 in one of 9 studied cases. One case was characterized by a t(14;18)(q32;q21)/ IGH-MALT1 translocation. Follow-up was available in 8 cases. All remain systemically well after a median time of 86.5 months (range: 40 to 144 mo). Local recurrence of disease was observed in 3 patients. A fourth patient presented with a cMZL without amyloid deposits 8 years after excision of the cutaneous AL amyloidoma. Although our series is small, careful categorization and follow-up of the cases, together with updated information in the literature, show clinical and biological links between AL amyloidomas of the skin/subcutis and cMZL, suggesting that at least a subset of cutaneous AL amyloidoma may represent an unusual manifestation of cMZL (cutaneous mucosa-associated lymphoid tissue lymphomas).